The Emerging Role of the IL-17B/IL-17RB Pathway in Cancer - Bastid, Jérémy; Dejou, Cécile; Docquier, Aurélie; Bonnefoy, Nathalie (Frontiers in Immunology, 2020)
Among the inflammatory mediators, a growing body of evidence emphasizes the contribution of the interleukin 17 (IL-17) cytokine family in malignant diseases. Besides IL-17A, the prototypic member of the IL-17 family, several experimental findings strongly support a role for the IL-17B/IL-17 receptor B (IL-17RB) pathway in tumorigenesis and resistance to anticancer therapies. Mouse models indicate that IL-17B signaling through IL-17RB directly promotes survival, proliferation, and migration of cancer cells and induces resistance to conventional chemotherapeutic agents. More importantly, recent work from our team and others indicate that IL-17B signaling dramatically alters the tumor microenvironment by promoting chemokine and cytokine secretion which foster tumor progression. Strengthening results from the pre-clinical studies and relevance to the clinical situation, elevated IL-17B is associated with poor prognosis in patients with pancreatic, gastric, lung and breast cancer. We review here our current understanding of the IL-17B/IL-17RB signaling, expression patterns and biological activities in oncology and highlight issues that remain to be resolved to better characterize IL-17B and its receptor as potential targets for enhancing the efficacy of existing cancer therapies.